Synthesis of a self-reeling hose system for bathroom use - Zainal, Zairulazha; See, Hui Lin; Shamsudin, Shamsul Anuar; Al_Issa, Huthaifa Ahmad (Universiti Malaysia Perlis, 2022)
This work was carried out to design and test the self-reeling hose for bathroom use to achieve convenience and hygiene in the bathroom. The distribution of von Mises stress, displacement and safety factors were considered. SolidWorks, which is a solid modeling computer-aided design and engineering (CAD/CAE) software was used to integrate analysis and to help simulate physical interactions in engineering design such as stress, deflection and safety factors to match various parts of the self-reeling hose mechanisms. The House of Quality (HOQ) table was constructed to determine the engineering characteristics of the product. Three different design concepts were synthesized from the morphological chart and a design concept that was most critical to fulfilling the criteria was chosen using the method of Pugh concept selection. Consequently, the computer analysis and simulation for particular parts were done and the finalized assembly were presented. The bending force and torque of the ratchet and pawl system were calculated to ensure safety in its operation. Overall, the mechanism is safe to manufacture and use with the appropriate materials and design considerations.